Penggunaan Platform Pembayaran Digital E-Commerce di Sukabumi: Perbandingan Antara DANA dan ShopeePay - Leydia Maulidiawaty, Siti; Nizar, Auralea; Aulia Firdaus, Alya; Syariefa Bintang Maharani, Adinda; Muhammad Danial, R. Deni (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to analyze and compare the use of two popular digital payment platforms in Indonesia, DANA and ShopeePay, in the context of e-commerce transactions in the city of Sukabumi. By observing user preferences, advantages, and disadvantages of each platform, this study is expected to provide valuable insights for users, local e-commerce players, and digital payment application developers. The research method used involves quantitative and qualitative approaches through questionnaire surveys and interviews with e-commerce users in Sukabumi who actively use GoPay and OVO. The results of the study show significant differences in feature preferences, satisfaction levels, and obstacles faced by users of the two platforms. The implications of these findings provide a basis for the development of digital payment services that are more in line with local market needs.